Language, Culture and Spatial Cognition: Bringing anthropology to the table - Norbert Ross; Jeffrey T. Shenton; Werner Hertzog; Mike Kohut (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
Languages vary in their semantic partitioning of the world. This has led to speculation that language might shape basic cognitive processes. Spatial cognition has been an area of research in which linguistic relativity – the effect of language on thought – has both been proposed and rejected. Prior studies have been inconclusive, lacking experimental rigor or appropriate research design. Lacking detailed ethnographic knowledge as well as failing to pay attention to intralanguage variations, these studies often fall short of defining an appropriate concept of language, culture, and cognition. Our study constitutes the first research exploring (1) individuals speaking different languages yet living (for generations) in the same immediate environment and (2) systematic intralanguage variation. Results show that language does not shape spatial cognition and plays at best the secondary role of foregrounding alternative possibilities for encoding spatial arrangements.
Keywords: Linguistic Relativity Hypothesis; Culture; Language and Cognition; Language and Spatial Cognition